HOW SFG INCREASE STUDENTS ABILITY TO PRODUCE AND ANALYSE TEXT MEDIA - Ghofur, Abd. (OKARA: Jurnal Bahasa dan Sastra, 2013)
This article explores the use of Systemic Functional Grammar for students of english language teaching entitled Analysing Media Texts. This is aims at assisting students to produce their own texts and to help them develop an understanding of the linguistic choices they make. Students are introduced to the key principles of CDA and to Halliday’s SFG to provide them with tools to assist them to understand the social and constructed nature of discourses, especially those typically found in media texts. This article focuses on students’ interpretation of media texts, their ability to read with greater understanding and to apply key concepts that they had learnt to their analyses. The students demonstrated clearly that they had developed an understanding of CDA, acquired the basic metalanguage necessary for Hallidayan analysis and some of them could produce much more rigorous textual analyses than before.